2012
DOI: 10.1038/nchembio.944
|View full text |Cite
|
Sign up to set email alerts
|

YcaO domains use ATP to activate amide backbones during peptide cyclodehydrations

Abstract: Thiazole/oxazole-modified microcins (TOMMs) encompass a recently defined class of ribosomally synthesized natural products with a diverse set of biological activities. Although TOMM biosynthesis has been investigated for over a decade, the mechanism of heterocycle formation by the synthetase enzymes remains poorly understood. Using substrate analogs and isotopic labeling, we demonstrate that adenosine 5′-triphosphate (ATP) is utilized to directly phosphorylate the peptide amide backbone during TOMM heterocycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
232
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(247 citation statements)
references
References 36 publications
10
232
0
3
Order By: Relevance
“…The thiazolines are subsequently dehydrogenated by the flavin mononucleotide (FMN)-containing enzyme BcerB to form thiazole heterocycles (Fig. 5A) (28,29). HSEE analysis indicated that for the intermediate containing one thiazole ring (loss of 20 Da) the structure containing a C-terminal thiazole has the highest Hs values (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The thiazolines are subsequently dehydrogenated by the flavin mononucleotide (FMN)-containing enzyme BcerB to form thiazole heterocycles (Fig. 5A) (28,29). HSEE analysis indicated that for the intermediate containing one thiazole ring (loss of 20 Da) the structure containing a C-terminal thiazole has the highest Hs values (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…YcaO domain proteins activate backbone amide bonds by phosphorylation26, 27 or adenylation28 of the carbonyl oxygen, and all YcaO domain proteins with a characterized activity have a partner cyclodehydratase that aids catalysis of cyclization to oxazolines or thiazolines 29. The bottromycin gene cluster encodes two YcaO domain proteins, BtmE and BtmF, but no cyclodehydratases.…”
mentioning
confidence: 99%
“…[6] BalhD is homologous to the C-terminal 400 residues of TruD, whilst a second protein BalhC matches the N-terminal 300 residues ( Figure S2). When both BalhD and BalhC are present heterocyclization of the microcin substrate is accelerated and only when both proteins are present can phosphate release be robustly measured.…”
mentioning
confidence: 99%
“…The immediate sequence context and position (relative to the leader) of the target cysteine is variable. a kinase type mechanism in which a hemiorthoamide intermediate is phosphorylated [6,7] ( Figure S3). The cyanobactin class of heterocyclases, exemplified by TruD, possess an almost unique combination of processivity, specificity, chemical versatility, and promiscuity, which thus makes them a fascinating subject for study.…”
mentioning
confidence: 99%
See 1 more Smart Citation